Pathology of Pigmented Skin Lesions - Plaza, Jose A.; Prieto, Victor G.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book offers a practical approach to the histologic analysis of a wide range of melanocytic skin lesions, including various nevi and different forms of melanoma, as well as pigmented non-melanocytic lesions. In addition, sentinel node biopsy findings and the use of special ancillary studies are covered in detail. Each chapter presents illustrative cases that document the route to correct diagnosis. An important feature of the book is the clinical-pathologic correlation of challenging melanocytic tumors; accordingly, it will appeal not only to pathologists (general surgical pathologists and dermatopathologists) but also to dermatologists (including dermatopathologists). The book contains some 250 color photos as well as tables and algorithms designed to assist in the diagnosis of difficult cases.
Pigmented, non-melanocytic lesions -- Ephelides and Lentigo -- Nevi -- Acquired Melanocytic Nevi -- Nevi of Special Sites -- Family of Blue Nevi -- Congenital Nevi -- Dermal Melanocytosis -- Spitz Nevi -- Dysplastic Nevi -- Melanoma -- Incipient Melanoma / Melanoma In situ -- Invasive Cutaneous Melanoma -- Nevoid Melanoma (including spitzoid melanoma) -- Mucosal Melanoma -- Sentinel Lymph Node -- Ancillary studies in challenging melanocytic tumors: Immunohistochemistry, FISH, CGH.
Keywords: Medicine; Dermatology; Oncology; Pathology; Medicine & Public Health; Pathology; Dermatology; Oncology